Collins Paperback Thesaurus - Published by HarperCollins (England HarperCollins Publishers, 1997)
This thesaurus contains an A-Z layout for easy reference and for each entry there is an alphabetical list of synonyms. At many entries there are also lists of antonyms which gives the useful option of using a word of opposite meaning.
Keywords: English language--Synonyms and antonyms -- English language -- Dictionaries